Modelling, simulation and performance analysis of a 3D image processing algorithm - Zhong, Chunpeng. (2012)
With the rapid development of computer software and hardware, the popularity of applications based on computer graphics in various industries is rapidly growing and becoming the most researched and developed branches of computer graphics. The core technology of these popular topics is 3D computer graphics. With the improvements of computer games industry, the computer hardware has been pushed to render complex 3D scenes at interactive rates. In order to achieve Real-time 3D rendering interactively, modern graphics card resorts to lower-quality shading techniques that are approximately well established, and much slower, high-quality methods. Besides computer games, 3D graphics has a wide range of applications like computer-aided design and manufacturing, 3D animated film and other television productions, aerospace, military, geological exploration and real-time simulation.